Arsenic in hydrothermal apatite: Oxidation state, mechanism of uptake, and comparison between experiments and nature. (1st January 2017) - Liu, Weihua; Mei, Yuan; Etschmann, Barbara; Brugger, Joël; Pearce, Mark; Ryan, Chris G.; Borg, Stacey; Wykes, Jeremey; Kappen, Peter; Paterson, David; Boesenberg, Ulrike; Garrevoet, Jan; et al.
Highlights: As(III) and As(V) both can be incorporated in hydroxylapatite during dynamic coupled dissolution/reprecipitation reactions. As(III) moieties replace phosphate groups with a high local strain compared to As(V). Upon recrystallization, As(V) replaces the As(III) in the hydroxylapatite structure. Most studied natural hydrothermal apatites retain mainly As(V), even though they formed from solutions that mainly contained As(III). Reaction pathway and kinetics exert a major controls on As(III) uptake in hydrothermal apatite. Abstract: Element substitution that occurs during fluid–rock interaction permits assessment of fluid composition and interaction conditions in ancient geological systems, and provides a way to fix contaminants from aqueous solutions. We conducted a series of hydrothermal mineral replacement experiments to determine whether a relationship can be established between arsenic (As) distribution in apatite and fluid chemistry. Calcite crystals were reacted with phosphate solutions spiked with As(V), As(III), and mixed As(III)/As(V) species at 250 °C and water-saturated pressure. Arsenic-bearing apatite rims formed in several hours, and within 48 h the calcite grains were fully replaced. X-ray Absorption Near-edge Spectroscopy (XANES) data show that As retained the trivalent oxidation state in the fully-reacted apatite grown from solutions containing only As(III). Extended X-ray Fine Spectroscopy (EXAFS) data reveal that these As(III) ions are surrounded by about three oxygen atoms at an AsO bond length close to that of an arsenate group (AsO4 3− ), indicating that they occupy tetrahedral phosphate sites. The three-coordinated As(III)–O3 structure, with three oxygen atoms and one lone electron pair around As(III), was confirmed by geometry optimization using ab initio molecular simulations. The micro-XANES imaging data show that apatite formed from solutions spiked with mixed As(III) and As(V) retained only As(V) after completion of the replacement reaction; in contrast, partially reacted samples revealed a complex distribution of As(V)/As(III) ratios, with As(V) concentrated in the center of the grain and As(III) towards the rim. Most natural apatites from the Ernest Henry iron oxide copper gold deposit, Australia, show predominantly As(V), but two grains retained some As(III) in their core. The As-anomalous amphibolite-facies gneiss from Binntal, Switzerland, only revealed As(V), despite the fact that these apatites in both cases formed under conditions where As(III) is expected to be the dominant As form in hydrothermal fluids. These results show that incorporation of As in apatite is a complicated process, and sensitive to the local fluid composition during crystallization, and that some of the complexity in As zoning in partially reacted apatite may be due to local fluctuations of As(V)/As(III) ratios in the fluid and to kinetic effects during the mineral replacement reaction. Our study shows for the first time that As(III) can be incorporated into the apatite structure, although not as efficiently as As(V). Uptake of As(III) is probably highly dependent on the reaction mechanism. As(III)O3 3− moieties replace phosphate groups, but cause a high strain on the lattice; as a result, As(III) is easily exchanged (or oxidized) for As(V) during hydrothermal recrystallization, and the fully reacted grains only record the preferred oxidation state (i.e., As(V)) from mixed-oxidation state solutions. Overall this study shows that the observed oxidation state of As in apatite may not reflect the original As(III)/As(V) ratio of the parent fluid, due to the complex nature of As(III) uptake and possible in situ oxidation during recrystallization.